PENGARUH BIMBINGAN KELOMPOK DENGAN TEKNIK SIMULASI TERHADAP SIKAP KEWIRAUSAHAAN SISWA SMK - Taufik Agung Pranowo; Iis Lathifah Nuryanto (Universitas Sultan Ageng Tirtayasa, 2020)
This study aims 1) to find out the implementation of group guidance services in Sudirman Islamic Vocational Schools, 2) to determine the conditions of student entrepreneurship attitudes in Islamic Sudirman Vocational Schools and 3) to determine the effect of group guidance with simulation techniques on student entrepreneurship attitudes in Islamic Sudirman Vocational Schools. This type of research is quantitative with experimental models. The population in this study amounted to 110 grade X students, while the study sample numbered 10 students. Data analysis using the Wilcoxon formula. The results of this study are 1) The implementation of group guidance services at Sudirman Islamic Vocational School has been running but has not yet focused on developing behavior specifically only focused on increasing students to follow the rules, 2) Conditions of entrepreneurial attitudes namely 32 (for the highest grades) and 6 ( the lowest value) for entrepreneurial attitudes, and 3) The results of the implementation of group counseling with simulation techniques showed that asymp sig results were obtained at 0.03 <0.05. The conclusion of this study, that group guidance with simulation techniques had a positive and significant effect on entrepreneurial attitudes of students at SMK Islam Sudirman.